VARIASI DAN KOMPOSISI TANAMAN MPTS PADA LAHAN AGROFORESTRI DI TIGA KEMIRINGAN LAHAN YANG BERBEDA (STUDI KASUS GAPOKTANHUT PUJOMAKMUR) - Maharanti, Danti; P. Harianto, Sugeng; Kartika Tsani, Machya; Asmarahman, Ceng (Jurnal Nusa Sylva, 2025)
The use of Multi-Purpose Tree Species (MPTS) in agroforestry systems on sloped area provides solutions in the ecological and economic fields of land management. The physiological and ecological characteristics of each type of plant influence its adaptability to slopes, its ability to resist erosion, as well as its contribution to soil fertility and agroforestry productivity. This research aims to identify the composition of MPTS species on three different slopes of land. The study was carried out by using direct observation in agroforestry area that include in three different type of land slopes, with category Moderate (8-15 %), Moderately steep (15-25 %), Steep (25-65 %). The reserach results show that there are different MPTS plant compositions on 3 different slopes of agroforestry area. In moderate slope, there are 10 species. Meanwhile, moderately steep category, there are 9 species, and in steep category there are 10 species. MPTS from jungle plantation type become dominated MPTS species in 8-15% and 25-60% slope, and agricultral MPTS is domintaed in 15-25% slope.